2022
DOI: 10.3389/fcimb.2022.925804
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Proteasomes in Cancer and Infectious Disease: A Parallel Strategy to Treat Malignancies and Microbes

Abstract: Essential core pathways of cellular biology are preserved throughout evolution, highlighting the importance of these pathways for both bacteria and human cancer cells alike. Cell viability requires a proper balance between protein synthesis and degradation in order to maintain integrity of the proteome. Proteasomes are highly intricate, tightly regulated multisubunit complexes that are critical to achieve protein homeostasis (proteostasis) through the selective degradation of misfolded, redundant and damaged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Multiple myeloma (MM) is a cancer of terminally-differentiated plasma cells (PCs) that accumulate and proliferate predominantly within the tumor permissive BM microenvironment ( 20 25 ). PCs are primary effectors of humoral immunity and function as antibody-producing factories that secrete vast amount of immunoglobulins.…”
Section: Linking Altered Cellular Metabolism To Multiple Myelomamentioning
confidence: 99%
“…Multiple myeloma (MM) is a cancer of terminally-differentiated plasma cells (PCs) that accumulate and proliferate predominantly within the tumor permissive BM microenvironment ( 20 25 ). PCs are primary effectors of humoral immunity and function as antibody-producing factories that secrete vast amount of immunoglobulins.…”
Section: Linking Altered Cellular Metabolism To Multiple Myelomamentioning
confidence: 99%
“…Worldwide, cancer and infectious disease are major causes of morbidity and mortality, and while the causative agents and molecular mechanisms of disease may differ, they share many pathophysiologic similarities [19,[102][103][104]. Proteasomes are conserved throughout evolution and contribute to the cell biology and viability of parasites, and unicellular and multicellular organisms [105][106][107].…”
Section: Targeting Proteasomes To Treat Infectious Diseasesmentioning
confidence: 99%
“…The 26S proteasome is a ~2.5 MDa, ATP-hydrolyzing proteolytic machine that functions as the protein-hydrolyzing catalytic core component of the UPS [16][17][18][19]. 26S proteasomes are assembled in an ATP-dependent reaction and are comprised of two subcomplexes, namely a 20S core particle (CP) and 19S regulatory particles (RPs, PA700) that cap either or both ends of the 20S CP [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the proteasome inhibitors bortezomib and carfilzomib have shown significant promise in targeting plasma cells that secrete HLA-antibodies and hinder organ transplantation ( Tremblay et al, 2020 ; Woodle et al, 2020 ). TGF-β/Smad signaling has been shown to regulate expression of the proteasome catalytic subunit PSMB5 ( Lai et al, 2018 ) and a number of studies suggest that PSMB5 contributes to proteasome inhibitor resistance ( Oerlemans et al, 2008 ; Ignatz-Hoover et al, 2022 ). Studies in bortezomib-resistant myelomonocytic cells revealed PSMB5 overexpression, mutations within the highly conserved bortezomib binding pocket in PSMB5 and that PSMB5 knockdown restored drug sensitivity.…”
Section: Tumor Intrinsic Effects Of Tgf-β Confers Drug Resistance In ...mentioning
confidence: 99%